2016
DOI: 10.1098/rsos.160616
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental parameters on movements and habitat utilization of humpback whales (Megaptera novaeangliae) in the Madagascar breeding ground

Abstract: Assessing the movement patterns and key habitat features of breeding humpback whales is a prerequisite for the conservation management of this philopatric species. To investigate the interactions between humpback whale movements and environmental conditions off Madagascar, we deployed 25 satellite tags in the northeast and southwest coast of Madagascar. For each recorded position, we collated estimates of environmental variables and computed two behavioural metrics: behavioural state of ‘transiting’ (consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 85 publications
(145 reference statements)
5
42
0
Order By: Relevance
“…This result is consistent with a hypothesis that deep-water transit could be comparable to trans-oceanic migration, while transit in shallow water could rather reflect roving movement, at lower speed, between suitable breeding sites (i.e., searching for localized patches of breeding whales). Mean travel speed during deep-water transit was within the range of speed reported during off-shore migration between feeding and breeding areas [11, 22, 23, 25, 28, 31]. In wintering areas generally, it was previously shown that whales usually travelled at slower speed [11, 22, 25, 31], although changes in movement behavior within and between breeding sites (localized vs. transit behavior) were not accounted for (excepted in [31]).…”
Section: Discussionmentioning
confidence: 72%
“…This result is consistent with a hypothesis that deep-water transit could be comparable to trans-oceanic migration, while transit in shallow water could rather reflect roving movement, at lower speed, between suitable breeding sites (i.e., searching for localized patches of breeding whales). Mean travel speed during deep-water transit was within the range of speed reported during off-shore migration between feeding and breeding areas [11, 22, 23, 25, 28, 31]. In wintering areas generally, it was previously shown that whales usually travelled at slower speed [11, 22, 25, 31], although changes in movement behavior within and between breeding sites (localized vs. transit behavior) were not accounted for (excepted in [31]).…”
Section: Discussionmentioning
confidence: 72%
“…The reasons for such extensive migrations are still debated but could be linked to increased calf fitness in warmer waters of the tropical and subtropical breeding grounds (Clapham, ). Although this hypothesis suggests a direct link between humpback whale life history and water temperature, it remains unclear how sea surface temperature (SST) drives distributions within breeding latitudes, as studies have shown both strong relationships (Bortolotto, Danilewicz, Hammond, Thomas, & Zerbini, ; Guidino, Llapapasca, Silva, Alcorta, & Pacheco, ; Rasmussen et al, ; Smith et al, ) and weak or no effects of this variable (Dulau et al, ; Trudelle et al, ). SST is dynamic, with complex changes through time as it fluctuates on multiple temporal scales (monthly, seasonally, annually) and follows patterns that may be stochastic, cyclic (e.g., El Niño Southern Oscillation [ENSO], Pacific Decadal Oscillation, Antarctic Oscillation [AAO]) or continuous (climate change).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for such extensive migrations are still debated but could be linked to increased calf fitness in warmer waters of the tropical and subtropical breeding grounds (Clapham, 2000). Although this hypothesis suggests a direct link between humpback whale life history and water temperature, it remains unclear how sea surface temperature (SST) drives distributions within breeding latitudes, as studies have shown both strong relationships (Bortolotto, Danilewicz, Hammond, Thomas, & Zerbini, 2017;Guidino, Llapapasca, Silva, Alcorta, & Pacheco, 2014;Rasmussen et al, 2007;Smith et al, 2012) and weak or no effects of this variable (Dulau et al, 2017;Trudelle et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent knowledge on baleen whales in the IO relies on coastal areas visual sighting or telemetry. For instance, humpback whale (Megaptera novaengliae) population in the western IO have been studied in their breeding areas throughout the austral winter (Kiszka et al, 2010;Trudelle et al, 2016) and Pygmy Blue Whale (PBW) (Balaenoptera musculus brevicauda) population have been observed in the eastern IO in their feeding areas throughout the austral summer (Gill et al, 2011;Double et al, 2014). However, these methods are expensive, require dedicated manpower and are often poorly efficient, especially in deep waters (Mellinger et al, 2007).…”
Section: Introductionmentioning
confidence: 99%